2017
DOI: 10.5935/abc.20170009
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with the Prescription of Antihypertensive Medications and Blood Pressure Control in Primary Care

Abstract: BackgroundHypertension is the most prevalent risk factor for cardiovascular disease, and its proper control can prevent the high morbidity and mortality associated with this disease.ObjectiveTo assess the degree of compliance of antihypertensive prescriptions with the VI Brazilian Guidelines on Hypertension and the blood pressure control rate in primary care.MethodsCross-sectional study conducted between August 2011 and November 2012, including 332 adults ≥ 45 years registered in the Family Doctor Program in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
2
12
1
2
Order By: Relevance
“…Findings from our secondary analysis of a population-based survey revealed that 82.7% of respondents used antihypertensive medication regularly. The level of antihypertensive medication adherence in Taiwan was similar to that reported in South America 12 and higher than the 50% reported in a Vietnamese study 13 and the 56% in a Middle East study. 14 A retrospective population-based study using the Taiwan National Health Insurance Research Database (NHIRD) found that 52.9% of patients had high antihypertensive medication adherence, which was defined as a medication possession ratio (MPR) ≥80%.…”
Section: Discussionsupporting
confidence: 77%
“…Findings from our secondary analysis of a population-based survey revealed that 82.7% of respondents used antihypertensive medication regularly. The level of antihypertensive medication adherence in Taiwan was similar to that reported in South America 12 and higher than the 50% reported in a Vietnamese study 13 and the 56% in a Middle East study. 14 A retrospective population-based study using the Taiwan National Health Insurance Research Database (NHIRD) found that 52.9% of patients had high antihypertensive medication adherence, which was defined as a medication possession ratio (MPR) ≥80%.…”
Section: Discussionsupporting
confidence: 77%
“…Studies on older patients receiving outpatient treatment have also identified high prevalence of concomitant use of ACE inhibitors and diuretics for blood pressure control. 23,24 Despite the greater effectiveness of this combination of antihypertensives, the combination of these medications increases the risk of orthostatic hypotension, especially among older people, with a risk of injury due to falls. 25 In a study conducted in the south of Brazil, the frequency with which patients used antidiabetics and antihypertensives was high, 26 due to high prevalence of diabetes mellitus and arterial hyperten- Among the drugs for which concomitant prescriptions are contraindicated, those that had the clinical effect of increasing the risk of prolonged QT interval were observed more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…There are certain contra indications for using each drug, and certain drugs are more preferred for co-morbid conditions. Certain western studies in urban scenario show excellent prescription compliance,[13] but similar studies are lacking in India. To maintain the competency of prescribing appropriate drug to the patients, family physician or general practitioner (GP) being the first contact of care should be regularly updated about recent changes in the management guidelines.…”
Section: Discussionmentioning
confidence: 99%